ORGANIZATIONAL CITIZHENSHIP BEHAVIOR MEMEDIASI PENGARUH KECERDASAN SPIRITUAL, KECERDASAN EMOSIONAL, KOMITMEN AFEKTIF TERHADAP KINERJA PEGAWAI - Edi Sumantri; yunita yunita; Andhi Johan Suzana; Herwiek Dyah Lestari (FEB UNWIKU PURWOKERTO, 2021)
This study aims to analyze the role of Organizational Citizenship Behavior (OCB) in mediating the influence of spiritual intelligence, emotional intelligence and affective commitment on the performance of employees of PT Wahana Kasih Mulia Kedungreja. The population in this study were 93 employees of PT Wahana Kasih Mulia Kedungreja. The sampling technique used proportional random sampling with a sample of 76 employees. The analysis uses regression and mediation effect analysis using the product of coefficient method. The results showed that spiritual intelligence, emotional intelligence, affective commitment and OCB had a significant positive effect on performance. The results of the mediation test of spiritual intelligence and affective commitment have a significant positive but not significant positive effect on emotional intelligence